APPLICATION OF REVERSE LEARNING TECHNOLOGY IN ENGLISH CLASSES IN MODERN EDUCATION - Ibadullayeva Мalika Khamdambek Qizi (Western European Studies, 2024)
This article explores the application of reverse learning technology in English classes as a modern educational approach. Reverse learning involves students taking on the role of teachers, creating engaging and interactive lessons that help enhance their understanding and retention of knowledge. The use of technology in this process further enhances student engagement and motivation in language learning. The article discusses the benefits and challenges of implementing reverse learning technology in English classes and provides practical recommendations for educators looking to incorporate this innovative approach into their teaching practices
Keywords: Reverse learning; technology; English classes; modern education